(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract:- One of the key values of the banking industry has been its ’Customer-Focused’ mindset, but in the new era, the trend is moving to being ’Customer-Centric’. This is because advances in technology and communication, combined with an explosive growth in data and information, have given rise to an even more empowered and aware global consumer. With this change in consumer dynamics; the banking industry has an opportunity to develop an improved customer engagement strategy. More than 70% of the banking executives worldwide say customer centricity is important to them, but do they really understand what that means? Being customer centric means; providing customer satisfaction in five core areas of the Customer-Bank relationship. The banks need to analyze their service and answer the following questions: